The effect of Scutellaria baicalensis on the signaling network in hepatocellular carcinoma cells. - Ye F; Che Y; McMillen E; Gorski J; Brodman D; Saw D; Jiang B; Zhang DY (Nutrition & Cancer)
Scutellaria baicalensis is an anti-inflammatory and antineoplastic Chinese herbal therapy. We have previously shown that S. baicalensis can inhibit hepatocellular carcinoma (HCC) cell growth in vitro. In this study, we sought to determine the effect of S. baicalensis on the cell signaling network using our newly developed Pathway Array technology, which screens cell signaling pathways involved in cell cycle regulation. The HCC cell line (HepG2) was treated with S. baicalensis extract in vitro. The effect on the cell cycle was analyzed by flow cytometry, and the expression of various signaling proteins was assayed with Pathway Array. Our results indicate that S. baicalensis exerts a strong growth inhibition of the HepG2 cells via G2/M phase arrest. The Pathway Array analysis of 56 proteins revealed a total of 14 differentially expressed proteins or phosphorylations after treatment. Of these, 9 showed a dose-dependent decrease (p53, ETS1, Cdc25B, p63, EGFR, ERK1/2, XIAP, HIF-2[alpha], and Cdc25C) whereas one demonstrated a dose-dependent increase (Cyclin E) after treatment with 200 µg/ml of S. baicalensis. Using computer simulation software, we identified additional hubs in the signaling network activated by S. baicalensis. These results indicate that S. baicalensis exerts a broad effect on cell signaling networks leading to a collective inhibition of cell proliferation.